Assessment of Anti-HBs Titre Among Healthcare Workers at a Tertiary Care Centre, Visnagar, Gujarat - Gaur, Bhumika; D Shah, Parul; Mishra, Apurba Anshuman (Journal of Neonatal Surgery, 2025)
Introduction: Healthcare workers (HCWs) are at increased risk of acquiring hepatitis B virus (HBV) infection through occupational exposure, but this risk can be effectively mitigated through hepatitis B vaccination. Aims: Our goal is to determine the sero-prevalence of anti-Hepatitis B surface (anti-HBs) antibodies among healthcare workers in a tertiary care setting, in order to evaluate the level of protection for those in these high-risk environments. Material and Methods: Serum samples from HCWs were analyzed at the Microbiology laboratory of Nootan Medical College and Nootan General Hospital in Gujarat. Aseptic collection of 3 ml of venous blood was performed using a vacutainer. The serum anti-HBs titers were measured through an Enzyme-Linked Immunoassay (ELISA). Results: Of the 280 HCWs included, 259 were vaccinated, and 21 were unvaccinated. HCWs were grouped into four categories which comprised of doctors from all disciplines (n=37), nursing staff (n=140), technicians (n=53) and housekeeping (n=50). Among various groups of HCWs, the vaccination rate was highest among doctors and nursing staff’s than the other groups. While comparing the anti-HBs titre among the unvaccinated HCWs, it has been seen that out of 21 unvaccinated HCWs, majority of them (n=18) were having titre below 10 mIU/ml while few of them (n=3) had titres above 10mIU/ml. Conclusion: All healthcare workers should undergo regular screening for HBs antigen, receive a booster dose, and have their anti-HBs titers monitored.